DED-LB/M and in-situ alloying of a Co-Cr alloy with elemental powders: Defect formation, microstructure and mechanical properties - Stephan, Marcel; Maier, Andreas; Tangermann-Gerk, Katja; Frankl, Sebastian; Röhr, Manuel; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2024)
Many industrial sectors are facing regulations to reduce particulate pollution and avoid environmentally harmful manufacturing processes. At the same time, service lifetime of products needs to be improved. All these cases require high-performance materials and advanced processes to meet the requirements. Co-Cr alloys are considered promising materials for a wide range of respective applications due to their excellent wear and corrosion resistance. In this study, Additive Manufacturing by Laser Directed Energy Deposition of Metals in combination with the innovative approach of in-situ alloying was investigated to modify the resulting material properties of a Co-Cr alloy by additions of elemental Cr and Mo. First, the generated specimens were analyzed regarding cracks and relative density. Chemical composition was determined using optical emission spectrometry and energy dispersive X-ray spectroscopy. The microstructure was investigated by means of light microscopy and material hardness profiles were generated. It was found that the resulting properties can be specifically and flexibly adapted by in-situ alloying.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Additive Manufacturing; Directed Energy Deposition; in-situ alloying; material properties; microstructure